Cutting-Edge Care: Innovative Approaches to Cataract Surgery Counseling - Akshay Wagh; Shivraj Tagare; Swati Upadhaya; Rengaraj Venkatesh (Delhi Journal of Ophthalmology)
Counselling is an essential part of patient care, especially during the post-operative period, which can be challenging for patients. Cataract surgery patients require adequate counselling to understand the post-operative instructions, medications, and potential complications. However, one-on-one counselling can be time-consuming, especially in high-volume centers. To address this issue, a new approach called “Coffee with Counselling” has been introduced, which involves daily group counselling sessions for patients who have undergone surgery and their caregivers. The sessions include a 4-minute video that explains post-operative advice and instructions, displayed on a TV monitor while patients can drink coffee. After the video, a sister explains post-operative medications, and patients can ask questions and clear their doubts. The approach has several advantages over one-on-one counselling, including reduced counselling time, patients’ ability to ask questions in a group setting, creating a sense of community, and allowing family members to understand post-operative instructions and medications. The Coffee with Counselling approach is an innovative and practical way to provide patients with the necessary information and support during their recovery in a group setting. Healthcare professionals should consider adopting this approach to improve patient care and support.